KAJIAN DAMPAK INSIDER OWNERSHIP, EXTERNAL OWNERSHIP DAN LEVERAGE TERHADAP NILAI PERUSAHAAN. (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di BEI Periode 2009-2015) - Banter Laksana (Jurusan Akuntansi Politeknik Negeri Bandung, 2017)
Abstract: This study aims to test empirically the effect Leverage, insider ownership, and external ownership to firm value. The population of this research is manufacturing companies listed in Indonesia Stock Exchange in the period 2009 to 2015. The data collection method used is purposive sampling, and gained as much as 113 sample. Testing of the entire hypothesis in this study using path analysis, through Amos program package version 16.0 for Windows. The results of this study indicate that ownership by internal and external parties could encourage managers in decision making for external financing (leverage) to increase the value of the company. The findings of this study may indicate that the investment of mediation shareholding by external influences on firm value.Keywords: Leverage, insider ownership, and external ownership, and the firm value